Mental Health Beliefs and Their Relationship With Treatment Seeking Among U.S. OEF/OIF Veterans. Issue 3 (16th May 2014) - Vogt, Dawne; Fox, Annie B.; Di Leone, Brooke A. L.
Abstract: Many veterans who would benefit from mental health care do not seek treatment. The current study provided an in‐depth examination of mental health‐related beliefs and their relationship with mental health and substance abuse service use in a national sample of 640 U.S. Operation Enduring Freedom and Operation Iraqi Freedom (OEF/OIF) veterans. Both concerns about mental health stigma from others and personal beliefs about mental illness and mental health treatment were examined. Data were weighted to adjust for oversampling of women and nonresponse bias. Results revealed substantial variation in the nature of OEF/OIF veterans' mental health beliefs, with greater anticipated stigma in the workplace ( M = 23.74) than from loved ones ( M = 19.30), and stronger endorsement of negative beliefs related to mental health treatment‐seeking ( M = 21.78) than either mental illness ( M = 18.56) or mental health treatment ( M = 20.34). As expected, individuals with probable mental health problems reported more negative mental health‐related beliefs than those without these conditions. Scales addressing negative personal beliefs were related to lower likelihood of seeking care ( OR s = 0.80–0.93), whereas scales addressing anticipated stigma were not associated with service use. Findings can be applied to address factors that impede treatment seeking.